Leishmania Parasite Subunit Vaccine in HLA-A2 Transgenic Mouse Model - H Rezvan (Iranian Journal of Public Health, 2005)
In the last few decades, parasitic infections have created a major human health problem across the world. In developing countries the problem is beyond control and the number of new cases is on a continuous rise. Leishmaniasis is a tropical disease affecting large number of population. Development of an effective and inexpensive vaccine represents a practical way to control this disease, as available chemotherapy is always accompanied by sever side effects. The major surface glycoproteins of the Leishmania parasites, gp63 and HASP-B1 have been postulated to be good candidates for vaccine development. In this study Leishmania parasite gp63 and HASP-B1 antigens were screened for potential immunogenic CTL epitopes (peptides) in HLA-A2 (HHD) transgenic mice. Three peptides given the code names of C1, C2 and B8 derived from gp63 were tested in HHDII mice for their immunogenicity. Two peptides (C2 and B8) were shown to be highly immunogenic following one in vivo immunisation however, 2 immunizations were needed to improve the immunogenicity of the C1 peptide. These results were also confirmed by INF-γ and IL-4 profiles in cultured spenocytes. In contrast to IL-4, the amount of INF-γ in splenocytes cultured with relevant immunogenic peptides was significantly higher than those in controls.